Exile and Return, The Babylonian Context - Stökl, Jonathan; Waerzeggers, Caroline (De Gruyter, 2015)
This collection of essays explores new ways of understanding the Babylonian Exile and the return to Yehud &#8211 a formative period in ancient Judaism. Drawing among others on new materials from cuneiform texts, the contributions study how Judean and other exiles interacted with the host society and vice versa, the way in which various biblical books reflect Babylonian culture, and the return migration to Jerusalem.
Keywords: Babylonian Exile; Cultural Contact; Return Migration; Second Temple Judaism